Zosteriform connective tissue nevus. - Garofalo, L. (European Journal of Pediatric Dermatology, 2015)
Lesions of connective tissue nevus type can be present in some inherited diseases such as tuberous sclerosis, Buschke-Ollendorf syndrome and family collagenoma or constitute an isolated finding. The isolated connective tissue nevus is histologically characterized by an accumulation of collagen fibers without a corresponding increased number of fibroblasts; in the connective tissue nevi besides the collagen fibers, which are usually increased, other components of the connective tissue such as the elastic fibers and the glycosaminoglycans of the fundamental substance can be involved; the elastic fibers can be increased, normal or decreased (1, 2). The isolated zosteriform connective tissue nevus, defined this way for its segmental distribution, is a rare disease, because less than 10 cases in the world literature have been described.